THE RELEVANCE BETWEEN THE THEORY OF PUBLIC SERVICE QUALITY WITH THE QUALITY OF PUBLIC SERVICES IN THE OFFICE OF POPULATION AND CIVIL REGISTRATION OF BARRU DISTRICT. - Kamaruddin Hasan; A. Ariyadi (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal